2008
DOI: 10.1177/0091270008317305
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Using a Single Postdose Midazolam Concentration to Predict CYP3A‐Mediated Drug Interactions

Abstract: Midazolam is a common probe used to predict CYP3A activity, but multiple blood samples are necessary to determine midazolam's area under the concentration-time curve (AUC). As such, single sampling strategies have been examined. The purpose of this study was to assess the ability of single midazolam concentrations to predict midazolam AUC in the presence and absence of CYP3A modulation by Ginkgo biloba extract (GBE). Subjects received oral midazolam 8 mg before and after 28 days of GBE administration. Postdose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 15 publications
1
30
2
Order By: Relevance
“…The purpose was to assess the ability of one single midazolam concentration for predicting midazolam AUC in the presence and absence of CYP3A modulation by Gingko biloba inducing CYP3A. The study showed that optimal midazolam sampling times to predict AUC were different before or after Gingko biloba [12]. This approach is not useful for prospective clinical trials where CYP3A activity is to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose was to assess the ability of one single midazolam concentration for predicting midazolam AUC in the presence and absence of CYP3A modulation by Gingko biloba inducing CYP3A. The study showed that optimal midazolam sampling times to predict AUC were different before or after Gingko biloba [12]. This approach is not useful for prospective clinical trials where CYP3A activity is to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Individual midazolam plasma concentrations were available during CYP3A baseline (n = 116), inhibition (n = 75), and induction or activation (n = 66) conditions from seven published studies (Table 1) [5,6,11,[21][22][23][24]. The data were from healthy adults, as determined by medical history, physical examination, and blood and urine laboratory tests, who were administered various single doses of oral midazolam alone or with the known CYP3A inhibitors: ketoconazole or doublestrength grapefruit juice or the known CYP3A inducers/activators: Ginkgo biloba extract, pleconaril, or rifampin.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The lower limit of quantitation ranged from 0.025 ng/ mL to 1 ng/mL, while inter-and/or intra-assay precision and accuracy was < 12%. Details of each assay are specified elsewhere [5,6,11,[21][22][23][24].…”
Section: Sample Collection and Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Institutional Review Board exemption was obtained from the University of California, San Diego, Human Research Protections Program. Midazolam plasma concentration data from 9 studies and serum concentration data from a single study were pooled from previously published studies of healthy subjects . Because the majority of studies consisted of plasma concentrations, a conversion factor was not used for the single study (n = 13) that used serum concentrations.…”
Section: Methodsmentioning
confidence: 99%